O(2) Chemistry of Dicopper Complexes with Alkyltriamine Ligands. Comparing Synergistic Effects on O(2) Binding - Company, Anna (2006)
Two dicopper(I) complexes containing tertiary N-methylated hexaaza ligands which impose different steric constrains to the Cu ions have been synthetized, and their reactivity towards O(2) has been compared with a mononuclear related system, highlighting the importance of cooperative effects between the metal centers in O(2) activation.